Challenges of an established amateur sport: Exploring how wheelchair basketball grows and thrives through a sport development lense - Pate, Joshua R; Bragale, Danielle (Journal of Amateur Sport, 2019)
Wheelchair basketball has been played in the United States for more than 70 years, and the National Wheelchair Basketball Association (NWBA) governing body has professionalized the sport to some extent with a league and culminating annual championship for its eight divisions. However, teams continue to face challenges that characteristically align with those of amateur sport in addressing recruiting and retaining athletes. The purpose of this study was to examine the challenges elite, competitive wheelchair basketball programs face and to understand their approach to recruiting and retaining athletes with disabilities to play the sport. Green’s (2005) theory of sport development was chosen as the lens for this study because of its focus on establishment of a sport for sustainability through athlete participation. An online open-ended questionnaire was sent to all 139 NWBA team contacts, with 28 responses representing multiple divisions within the league. Findings revealed that teams were primarily formed through unstable means of personal interest and community needs as well as stable means of university and rehabilitation hospital systems. Participants identified funding as the biggest challenge as they offered little support for tournament travel or financial rewards for athletes. Teams recruited athletes through social connections and community presence, but offered little structure for their means of retaining athletes. These findings show the NWBA teams operate with challenges akin to amateur sport due to uncertainty of funding and athlete sustainability.